Clergy Self-Care: Finding a Balance for Effective Ministry - Oswald, Roy M. (Rowman & Littlefield Publishers, 1991)
Nationally known for his work and teaching on clergy development, Oswald integrates research and experience into a liberating perspective on the pastoral calling. Discover how imbalances in your physical, emotional, spiritual, and intellectual lives can destroy the very ministry you seek to carry out. Learn what you can do to restore that balance. Packed with self-assessment tools, real-life experiences, and specific self-care strategies.